Hubungan Pengetahuan Ibu dan Dukungan Keluarga dengan Pemilihan Penolong Persalinan di Wilayah Kerja Puskesmas Pajagan Kecamatan Sajira Kabupaten Lebak - Rahmadhena, Melisa Putri; Handayani, Dwi Rizka Shofiana (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The MMR in West Java Province in 2022 was recorded at 127/100,000 live births, while the National MMR reached 189/100,000 live births, while the IMR in Banten Province was 13.8 per 1000 live births.To determine the relationship between maternal knowledge and family support and the selection of birth attendants in the work area of the Pajagan Health Center, Lebak Regency in 2023. Use analyst by designcross sectional The research population was 225 respondents in the third trimester of pregnancy at the Pajaan Community Health Center. The research sample consisted of 54 respondents.bivariate analysis eusing testShapiro Wilk Test. Test resultsShapiro wilk Test earned value 0.000 (p>0.05). So it can be concluded that there is no relationship between maternal knowledge and family support and the selection of birth attendants in the work area of the Pajagan Public Health Center, Lebak Regency. The conclusion was that there was no relationship between maternal knowledge and family support and the selection of birth attendants in the work area of the Pajagan Community Health Center, Lebak Regency. Suggestions in this research are for educational institutions, for research sites, for respondents and for future researchers. Keywords: Third Trimester Pregnant Mother, Birth Assistant  ABSTRAK AKI di Provinsi Jawa Barat tahun 2022 tercatat sebanyak 127/100.000 kelahiran hidup, Sementara AKI Nasional mencapai 189/100.000 kelahiran hidup, sedangkan AKB di Provinsi Banten di angka 13,8 per 1000 kelahiran hidup.  Mengetahui hubungan antara pengetahuan ibu dan dukungan keluarga dengan pemilihan penolong persalinan di wilayah kerja puskesmas pajagan kabupaten lebak tahun 2023. Menggunakan analitik dengan desain cross sectional Populasi penelitian adalah ibu hamil trimester III di Puskesmas Pajaan sebanyak 225 responden. Sampel penelitian berjumlah 54 responden.  analis bivariat emenggunakan uji Shapiro Wilk Test. Hasil uji Shapiro wilk Test diperoleh nilai 0,000 (p>0,05). sehingga dapat disimpulkan tidak ada hubungan antara pengetahuan ibu dan dukungan keluarga dengan pemilihan penolong persalinan di wilayah kerja puskesmas pajagan kabupaten lebak. Simpulan didapatkan tidak ada hubungan antara pengetahuan ibu dan dukungan keluarga dengan pemilihan penolong persalinan di wilayah kerja puskesmas pajagan kabupaten lebak. Disaran dalam penelitian ini untuk Institusi pendidikan, untuk tempat penelitian, untuk responden dan untuk peneliti selanjutnya. Kata Kunci: Ibu Hamil Trimester III, Penolong Persalinan